2017
DOI: 10.1007/s00429-017-1391-5
|View full text |Cite
|
Sign up to set email alerts
|

Hilar granule cells of the mouse dentate gyrus: effects of age, septotemporal location, strain, and selective deletion of the proapoptotic gene BAX

Abstract: The dentate gyrus (DG) principal cells are glutamatergic granule cells (GCs) and they are located in a compact cell layer. However, GCs are also present in the adjacent hilar region, but have been described in only a few studies. Therefore we used the transcription factor prospero homeobox 1 (Prox1) to quantify GCs at postnatal day (PND) 16, 30 and 60 in a common mouse strain, C57BL/6J mice. At PND16, there was a large population of Prox1-immunoreactive (ir) hilar cells, with more in the septal than temporal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 76 publications
0
22
1
Order By: Relevance
“…The outline of the hilus and GCL was drawn manually, and automated counts of cells based on size and circularity parameters were performed for both areas. We manually confirmed the accuracy of the threshold technique in every section, which we have previously discussed [57]. Quantification of double labeling for c-fos and GluR2/3 in the hilus was performed manually using 40x images.…”
Section: Methodsmentioning
confidence: 78%
“…The outline of the hilus and GCL was drawn manually, and automated counts of cells based on size and circularity parameters were performed for both areas. We manually confirmed the accuracy of the threshold technique in every section, which we have previously discussed [57]. Quantification of double labeling for c-fos and GluR2/3 in the hilus was performed manually using 40x images.…”
Section: Methodsmentioning
confidence: 78%
“…The background strain of these mice was a combination of C57BL6 and Sv129 (Bermudez‐Hernandez et al, ; Sahay et al, ). For breeding, Bax f/f female mice were bred with NestinCreER T2+/‐ Bax f/f male mice and the progeny were genotyped (Supporting Information Table S1) in‐house for the presence of Cre recombinase.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence was conducted as described previously (Bermudez‐Hernandez et al, ). Free‐floating sections were washed in 0.1 M TB, incubated in blocking serum for 1 hr (10% goat serum, 0.025% (v/v) Triton X‐100 and 0.005% (v/v) bovine serum albumin in 0.1 M Tris buffer), followed by washes in 0.1 M TB.…”
Section: Methodsmentioning
confidence: 99%
“…53 Many years later, it was also shown that the GCs might emerge from the septohippocampal zone, 54 or the hilus itself, because progenitors and young GCs appear to be present in the hilus normally. 55 When recordings were made of the hilar "ectopic" granule cells (EGCs), it was shown that they have axons that innervate normal GCs and CA3 pyramidal cells, possibly mediating the synchronization needed for a seizure focus. 56 Therefore, there was a new reason to think of the epileptic DG and CA3 as a potential focus.…”
Section: Adult Neurogenesis In Tlementioning
confidence: 99%
“…Immature GCs arise from progenitors that are mainly beneath the GCL but can be in the hilus. 55 Many types of GABAergic neurons (red) are added to the diagram because of the greater understanding that they normally are present. GABAergic neurons are named using a different classification system.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%